Respuesta :

Answer:

Liam is right.

Step-by-step explanation:

The transformation that demonstrate the congruence between these two triangles is the given one by Liam:

[tex]\triangle ABC[/tex] can be reflected over the y-axis to create [tex]\triangle EFD[/tex]

You can get this answer by observing the given graph. You can realize that one triangle is a reflection of the other across y-axis, because when this happens, the x-coordinates are changed by their opposite. There you can see that

x = -7 is changed to x' = 7

x = -3 is changed to x' = 3

x = -2 is changed to x' = 2

Therefore, the right transformation is the reflection accross y-axis given by Liam, he's right.

ACCESS MORE